The Significance of Cultural Heritage Preservation Enhancing Tourism Experience in Lapland - Kakonius, Chrislane (2024)
This bachelor’s thesis examines the significance of cultural heritage preservation in enhancing tourism in the region of Lapland, renowned for its unique Indigenous Sami cultural heritage and breathtaking natural landscapes. The research interacts with UNESCO's (2019) definition of cultural heritage, which includes tangible artefacts and intangible practices. It is debated that cultural heritage preservation is important for maintaining the unique identity of local communities, endorsing responsible tourism that benefits both visitors and residents. The interaction between cultural heritage and the primary emphasis of the study is on tourism dynamics. The research employs a mixed-methods approach, merging qualitative and quantitative data collection methods to provide a complete understanding of the identified issues. Data were collected or gathered through interviews with the HR manager, surveys, and observational research conducted during an internship in Lapland. The results indicated that respondents widely agree on the importance of cultural heritage in enhancing the tourism experience, with 80% of participants affirming its important role. Nevertheless, challenges such as the commodification of cultural practices and the phenomenon of excessive tourism were identified, underscoring the importance of careful oversight to prevent cultural degradation. From the perspective of social responsibility and authenticity, the research emphasises the importance of involving the Sami community in the development of tourism projects. This involvement serves to guarantee that cultural expressions remain authentic and respectful. Various strategies for effective conservation and promotion of cultural heritage are proposed, encompassing collaborative approaches, cultural education initiatives, and sustainable tourism practices. The thesis concludes that emphasizing cultural heritage preservation can promote sustainable tourism development, enhancing the visitor experience while supporting the Sami community and protecting ...